Effects of Combination of Ketamine with NorBNI on DREAM Protein and Ketamine-Induced Antinociceptive Effect in Formalin-Induced Inflammatory Pain - Long, Idris; Suppian, Rapeah; Ismail, Zalina (Journal of Physiological and Biomedical Sciences, 2017)
Downstream Regulatory Element Antagonist Modulator (DREAM) protein modulates pain by regulating c-Fos and prodynorphin genes transcription. The present study investigates the changes of DREAM protein expression in rat’s spinal cord and ketamine-induced antinociceptive effects upon the combining administration of ketamine and nor-binaltorphimine dihydrochloride (norBNI) following formalin-induced pain. Male Sprague Dawley rats were divided into several groups: rats administered with normal saline (C), rats given only formalin injections (F), rats treated with preemptive administration of either nor BNI (N+F) or ketamine (K+F) with formalin injections, and the combination of norBNI and ketamine (NK+F) administration with formalin injection. Formalin (5%) was injected subcutaneously to the rats’ hind paws, and the pain behavior was recorded for one hour. After two hours, the rats were sacrificed, and their spinal cords (L4-L5) were removed for western blot analysis. Results: Ketamine-induced antinociceptive effect on the pain behavior responses were apparently suppressed following the combination with norBNI (NK+F). However, there was no change in spinal DREAM protein levels detected between K+F and NK+F group. Conclusion: The suppression effect of the ketamine-induced antinociceptive effect was attenuated when combined with norBNI, though not through the modulation of genes transcriptional mechanism regulated by the DREAM protein.